2010
DOI: 10.1177/1759720x10365969
|View full text |Cite
|
Sign up to set email alerts
|

Management of antiphospholipid syndrome

Abstract: The antiphospholipid syndrome (APS) is an autoimmune disorder presenting with tissue injury in various organs related to large-or small-vessel thrombosis associated with antiphospholipid and antiprotein/phospholipid complex antibodies. Although the pathophysiology, diagnosis, and clinical scenario may seem clear and straightforward, a more detailed examination reveals a more complex and uncertain picture related to the management of APS. This article reviews the current situation relating to APS therapy by eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Refractory APS, whether primary or secondary and catastrophic APS could be the appropriate targets for these therapies currently [61]. …”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory APS, whether primary or secondary and catastrophic APS could be the appropriate targets for these therapies currently [61]. …”
Section: Managementmentioning
confidence: 99%
“…Moreover, treatment SLE-APS patients with HSCT and rituximab appears to be promising also, but further investigation and more clinical trials are required to evaluate the safety profile of these drugs, to identify the patients suitable for these aggressive therapeutic approaches and to know the effect of these approaches as long term cures of APS. Refractory APS, whether primary or secondary and catastrophic APS could be the appropriate targets for these therapies currently [ 61 ].…”
Section: Managementmentioning
confidence: 99%
“…Many patients, particularly those with primary HGP, will require no specific treatment, however, where attacks of rash and joint pains are frequent or debilitating successful therapy with colchicines, prednisolone, hydroxychloroquine, indomethacin, chlorambucil, rituximab and plasmapheresis have all been reported [4,5,7]. The antimalarial drug, hydroxychloroquine, appears to reverse platelet activation induced by human immunoglobulin aPL antibodies and decrease the thrombogenic properties of aPL antibodies and also appears to decrease aCL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Contraception in these patients is best by copper or LNG IUCD. Estrogen-containing hormonal contraceptives may be used in stable, inactive SLE patients but are contraindicated in patients with positive aPL antibodies [7].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of APLS usually requires long‐term warfarin therapy with an international normalized ratio goal of 2–3 (Kearon et al , ). Patients with elevated antiphospholipid antibody levels and a history of arterial or venous thrombosis are at a higher risk of recurrence and are usually placed on lifelong warfarin therapy (Del Papa & Vaso, ). Finnazi () reported that the incidence of non‐Hodgkin lymphoma was significantly higher in patients with APLS than in the general population, suggesting that APLS may be a risk factor for the development of non‐Hodgkin lymphoma.…”
mentioning
confidence: 99%